Impact of Infectious Diseases Consultation on Mortality in Patients with Candidemia. (4th October 2017) - Mejia, Carlos; Kronen, Ryan; Lin, Charlotte; Hsueh, Kevin; Powderly, William; Spec, Andrej
Abstract: Background: An infectious diseases (ID) consultation is often, but not always, obtained to help guide treatment of patients with candidemia. We examined if ID consultation affected patient outcome in patients with culture positive candidemia. Methods: We assembled a retrospective cohort of 1, 873 cases of candidemia in patients hospitalized in our academic tertiary care hospital from 2002 to 2015. We collected data on comorbidities, predisposing factors; antifungal therapy, survival and ID consult. Patients who died within 24 hours of diagnosis were excluded, under the presumption that they did not have an opportunity to receive an ID consult. Survival analysis was performed via univariate and multivariate Cox Regression with censoring at 90 days, as subsequent mortality was less likely to be related to candidemia. Results: 913 (49%) of the candidemic patients received an ID consult; 960 (51%) did not. Underlying comorbidities were evenly distributed between patients with and without an ID consult, except that patients with an ID consult more frequently had a central line (39% vs. 26%, p < 0.001), were on mechanical ventilation (4% vs. 2%, P = 0.003) or were receiving extracorporeal membrane oxygenation (2.2% vs. 0.5%, p = 0.002). The ID consult group had lower 90-day mortality compared with patients without an ID consult (34% vs. 49%, P < 0.001), with an adjusted hazard ratio of mortality for those patients receiving an ID consult of 0.55 (95% CI: 0.48, 0.64, P < 0.001) (Fig 1). Patient management differed significantly: the ID consult group was more likely to receive an echinocandin (29% vs. 21%, P < 0.001) or amphotericin B (AmB) (3.4% vs. 1.4%, P = 0.006). Conclusion: Candidemic patients who received an ID consult were significantly less likely to die, and were more likely to receive therapy with amphotericin or an echinocandin. These data suggest that an ID consult should be an integral part of clinical care of patients with candidemia. Disclosures: W. Powderly, Merck: Grant Investigator and Scientific Advisor, Consulting fee and Research grant; Gilead: Scientific Advisor, Consulting fee; Astellas: Grant Investigator, Research grant; A. Spec, Astellas Pharma US, Inc.: Grant Investigator, Research grant